2020
DOI: 10.1038/s41467-020-15999-y
|View full text |Cite
|
Sign up to set email alerts
|

Astrovirus infects actively secreting goblet cells and alters the gut mucus barrier

Abstract: Astroviruses are a global cause of pediatric diarrhea, but they are largely understudied, and it is unclear how and where they replicate in the gut. Using an in vivo model, here we report that murine astrovirus preferentially infects actively secreting small intestinal goblet cells, specialized epithelial cells that maintain the mucus barrier. Consequently, virus infection alters mucus production, leading to an increase in mucus-associated bacteria and resistance to enteropathogenic E. coli colonization. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 50 publications
7
47
1
Order By: Relevance
“…Recently, Cortez et al identified that murine astrovirus (MuAstV) infects goblet cells in the small intestines of adult C57BL/6 mice [84]. Similar findings were observed by Kolawole et al, who found that HAstV VAI could infect goblet cells and sucrose isomaltose positive enterocytes in HIEs [85].…”
Section: Astrovirus (Family: Astroviridae Genus: Astrovirus)supporting
confidence: 58%
See 1 more Smart Citation
“…Recently, Cortez et al identified that murine astrovirus (MuAstV) infects goblet cells in the small intestines of adult C57BL/6 mice [84]. Similar findings were observed by Kolawole et al, who found that HAstV VAI could infect goblet cells and sucrose isomaltose positive enterocytes in HIEs [85].…”
Section: Astrovirus (Family: Astroviridae Genus: Astrovirus)supporting
confidence: 58%
“…Altered microbiota composition has also been noted in children, poultry, and bats with astrovirus infection [88][89][90][91]. To identify the contribution of the gut microbiota to astrovirus, Cortez and colleagues treated mice with broad-spectrum antibiotics (vancomycin, ampicillin, neomycin, and metronidazole) and found that antibiotic treatment significantly reduced virus infection and shedding [84]. Although the exact mechanisms have not been elucidated, murine astrovirus STL5 also induces IFN-λ [92].…”
Section: Astrovirus (Family: Astroviridae Genus: Astrovirus)mentioning
confidence: 99%
“…For these analyses, gene expression differences between conditions were ranked for individual subsets and transcriptional clusters by calculating differential expression under a generalized linear hurdle model ( 48 ). To generate gene ranks, gene-specific average log fold changes were multiplied by the absolute difference in the proportions of cells expressing the gene (1 × 10 −4 as a lower boundary) and the inverse of the Bonferroni-corrected P values, which were rescaled from 1 × 10 −7 to 1 to institute reasonable bounds in the ranking; this approach has been implemented previously ( 49 ) to synthesize information about average expression differences, the fraction of cells expressing the gene at all, and statistical assessments of significance. These ranks were used as inputs for gene set enrichment analysis ( 26 ) using GSEA Preranked with a classic enrichment statistic and chip-based gene collapsing on the basis of the Human_Symbol_with_Remapping_MSigDB.v.7.0 chip ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…Comparably, murine RV causes both diarrhea in neonatal mouse pups and spreads among littermates [171,172]. Recently, murine AstV were discovered in immunocompetent, as well as in chronically infected immunodeficient, mice [163,173,174]. These murine AstV generally cause asymptomatic infection and minimal pathology [163].…”
Section: Mouse Modelsmentioning
confidence: 99%